Anormalidades durante el desarrollo embrionario de sardina común, Strangomera bentincki en el ambiente natural - Vásquez,Paulina (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2010)
To describe and quantify morphological abnormalities during the embryonic development of Strangomera bentincki an area nearby the Itata River mouth was sampled during the reproductive season 2007. Abnormality levels (3-13 %) were coincident with reported levels for other Clupeids species inhabiting areas with similar environmental characteristics to the area studied. Type and abnormalities prevalence were coincident with those reported for other fish species. Blastopore irregular closing and the embryonic axis twist were the most frequent in the samples. These abnormality types would be caused by errors during the epiboly, which can occur spontaneously, influenced by internal or external factors.